2018
DOI: 10.18632/oncotarget.24192
|View full text |Cite
|
Sign up to set email alerts
|

c-Jun-dependent β3GnT8 promotes tumorigenesis and metastasis of hepatocellular carcinoma by inducing CD147 glycosylation and altering N-glycan patterns

Abstract: β3GnT8, a key polylactosamine synthase, plays a vital role in progression of various types of human cancer. The role of β3GnT8 in hepatocellular carcinoma (HCC) and the underlying mechanisms, however, remain largely unknown. In this study, we found that β3GnT8 and polylactosamine were highly expressed in HCC tissues compared with those in adjacent paracancer tissues. Overexpression of β3GnT8 promoted while knockdown of β3GnT8 inhibited HCC cell invasion and migration in vitro. Importantly, enhanced tumorigenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…CD147, also known as EMMPRIN, Basign, and HAb18G, is a widely expressed cell surface protein with multiple glycosylated forms. Previous studies have shown that lectins PHA-L, PHA-E, and LEL could directly bind to CD147 in many types of cancer cells [12,34,35]. In the present study, we identified CD147 as a lectin LCA-recognized membrane glycoprotein in EC cells.…”
Section: Discussionsupporting
confidence: 59%
“…CD147, also known as EMMPRIN, Basign, and HAb18G, is a widely expressed cell surface protein with multiple glycosylated forms. Previous studies have shown that lectins PHA-L, PHA-E, and LEL could directly bind to CD147 in many types of cancer cells [12,34,35]. In the present study, we identified CD147 as a lectin LCA-recognized membrane glycoprotein in EC cells.…”
Section: Discussionsupporting
confidence: 59%
“…Liu et al found that the N-glycan profiles of membrane proteins in BC tissues significantly changed compared to the adjacent normal ones (40). Furthermore, previous reports have demonstrated the N-glycan alterations were essential for tumorigenesis, proliferation, and metastasis via modifying critical proteins or triggering mechanisms involved in the maintenance of cell homeostasis, such as ERS (41)(42)(43)(44)(45). The 12 known subunits of OST complex play different roles in N-glycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors contribute to the occurrence of HCC, such as DNA mutation and methylation, hepatitis B virus infection, aflatoxin B1 exposure, and aberrant activation of multiple intracellular signaling pathways . Despite the development of standard treatment options, including tumor resection, percutaneous radiofrequency ablation, chemotherapy, and liver transplantation, there are still many patients who present insufficient response to therapy . It is worthy to note that a more clear understanding of pathogenesis of HCC will be helpful for defining the effective diagnostic and therapeutic targets for HCC.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Despite the development of standard treatment options, including tumor resection, percutaneous radiofrequency ablation, chemotherapy, and liver transplantation, there are still many patients who present insufficient response to therapy. 8 It is worthy to note that a more clear understanding of pathogenesis of HCC will be helpful for defining the effective diagnostic and therapeutic targets for HCC.…”
Section: Introductionmentioning
confidence: 99%